2010
DOI: 10.1080/09687761003657598
|View full text |Cite
|
Sign up to set email alerts
|

Effective e-learning? Multi-tasking, distractions and boundary management by graduate students in an online environment

Abstract: This paper reports the findings of a small-scale study that documented the use of information technology for learning by a small group of postgraduate students. Our findings support current knowledge about characteristics displayed by effective e-learners, but also highlight a less researched but potentially important issue in developing e-learning expertise: the ability of students to manage the combination of learning and non-learning activities online. Although multi-tasking has been routinely observed amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 8 publications
0
28
0
4
Order By: Relevance
“…When e-learning occurs this way, the engagement and skill challenges experienced by many e-learners are often resolved (Winter, Cotton, Gavin, & Yorke, 2010). Stated another way, scaffolding is a framework that enables the learner to pace learning and internalize knowledge as manageable chunks of learning (Baker, 2010;Kim & Hannafin, 2011;Lipscomb, Swanson, & West, 2004;Verenikina, 2008).…”
Section: E-learning: Designing For Engaged Learningmentioning
confidence: 99%
“…When e-learning occurs this way, the engagement and skill challenges experienced by many e-learners are often resolved (Winter, Cotton, Gavin, & Yorke, 2010). Stated another way, scaffolding is a framework that enables the learner to pace learning and internalize knowledge as manageable chunks of learning (Baker, 2010;Kim & Hannafin, 2011;Lipscomb, Swanson, & West, 2004;Verenikina, 2008).…”
Section: E-learning: Designing For Engaged Learningmentioning
confidence: 99%
“…Nonetheless, multitasking does not always have negative consequences and may even have beneficial cognitive outcomes [15]. Indeed, this study found out that up to 74 of university students report that multitasking provides them enjoyment.…”
Section: Discussionmentioning
confidence: 88%
“…At the same time, several recent studies suggest that multitasking does not always have negative outcomes and may even have beneficial cognitive outcomes [15]. For example, [39]found no significant correlation between media multitasking and a range of psychosocial well-being factors, including emotional positivity, sociability, and impulsivity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While opinions differ about how teachers and educational developers can address these challenges, most frequent in the literature is the view that e-learning requires design through scaffolding that is grounded in relevant learning theory and diverse experiences for interaction. This way, the engagement and skill challenges of some e-learners are generally resolved (Winter, Cotton, Gavin, & Yorke, 2010). Scaffolding is a framework that enables the learner to pace his or her learning and experience it as manageable chunks (Alias, 2012;Baker, 2010;Grady, 2006;Kim & Hannafin, 2011;Lipscomb, Swanson, & West, 2004;McKenzie, 2000;Verenikina, 2008).…”
Section: Scaffolding and Instructional Designmentioning
confidence: 99%